ANALYSIS OF THE RESULTS OF THE FRENCH NATIONAL TEAM'S PERFORMANCES AT THE 2024 OLYMPIC GAMES IN JUDO (Physical Culture and Sport: Scientific Perspective, 2024)
The article analyzes the results of the French national judo team's performances at the 2024 Olympic Games. To achieve this goal, the following methods were used in the study: analysis and generalization of scientific and methodological literature; analysis of the protocols of the 2024 Olympic Games judo matches.  The initial data of the performances were taken from the official website of the International Judo Federation (https://www.ijf.org/competition/2653). It has been established that athletes from 5 continents and 122 countries took part in the Olympic Judo Games, the total number of participants was 378, including 192 men and 186 women. An analysis of the results of the French national team's performances at the Olympic Judo Games over the past 40 years has shown that the French representatives have been among the top three for quite some time. The results of the French national team's performances at the 2024 Olympic Games in judo showed that out of 7 weight categories for men, 4 judokas (57 %) became winners of the competition: Mkheidze Luka (- 60 kg; 2 m), Gaba Joan-Benjamin (- 73 kg; 2 m), Ngayap Hambou Maxime-Gael (- 90 kg; 3 m) and Riner Teddy (+ 100 kg; 1 m). 1 athlete finished in 5th place (- 66 kg; Khyar Walide). Among women in 7 weight categories - 5 athletes (72 %) became winners of the competition (Boukli Shirine (- 48 kg; 3m), Buchard Amandine (- 52 kg; 3m), Cysique Sarah Leonie (- 57 kg; 3m), Agbegnenou Clarisse (- 63 kg; 3m), Dicko Romane (+ 78 kg; 3m)). 1 judoka made it to the Top 10 (Gahie Marie Eve (- 78 kg; 7 m)). The results of the medal standings of the countries participating in the 2024 Olympic Games in judo showed that the Japanese national team won the competition and confirmed its world leadership in judo. The French team was among the top three, confirming its claim to leadership in judo. The analysis of the French national team's performance at the 2024 Olympic Games in judo confirmed that its representatives have a strong team and are winners of the competition. Moreover, they have also been confirming their results for quite a long time, which is a claim to leadership.
Keywords: judo; Olympic Games; France; national team; analysis; results; performances